Investigation of HDD Ramp Unloading Processes with an Efficient Scheme (Advances in Applied Mathematics and Mechanics, 2021)
Ramp load/unload (L/UL) mechanisms are widely used to rest sliders in hard disk drives (HDDs).Loading/unloading a slider swiftly and smoothly is crucial in a HDD design. A novel, efficientsimulation scheme is proposed to investigate the behaviors of a head disk interface (HDI) inramp unloading processes. A dual scale model is enabled by decoupling the nano-meter scale changeof an air bearing and the micro- or milli-meter scale deformation of a suspension. A modifiedReynolds equation governing the air bearing was solved numerically. The slider design wascharacterized with performance functions. Three stages in an unloading process were analyzedwith a lumped parameter suspension model. Key parameters for the model were estimated with acomprehensive finite element suspension model. Finally, simulation results are presented fora commercial HDI design.